CVD diamond coated drawing dies: a review. Issue 4 (12th March 2021) - Lin, Qiang; Chen, Sulin; Shen, Bin; Sun, Fanghong
ABSTRACT: Drawing dies have been playing a momentous role in the cold-forming industry for centuries, and nowadays the drawn products such as wires and tubes are adopted for a wide spectrum of applications. With the increased demand of productivity and quality of drawn products, which give higher requirements on the mechanical and tribological performance of the working surface of drawing dies, a variety of drawing dies have been developed during recent decades. In this case, the diamond-coated dies fabricated via chemical vapor deposition (CVD) demonstrate huge prospects in modern drawing production and have been vigorously studied in light of the superior performance. This paper is committed to reviewing the state-of-the-art development and applications of CVD diamond-coated drawing dies. In this letter, recent developments of drawing dies are briefly reviewed, particular attention is paid to the design and the fabrication of diamond-coated drawing dies, and finally, the applications of different diamond-coated dies are summarized.